2018
DOI: 10.1007/s00262-018-2239-4
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific response to nivolumab in patients with non-small cell lung cancer (NSCLC)

Abstract: In conclusion, the efficacy of immunotherapy is dependent on the metastatic location. Treatment appears more active in lymph nodes compared to other organ sites such as liver, adrenals and bone. Future strategies may include additional local treatment in case of oligoprogression in these organs in patients with otherwise sustained treatment benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 27 publications
7
94
0
Order By: Relevance
“…This study demonstrated that the tumor response to PD-1 inhibitors in HCC varied among different organs ( Table 2). This diversity of organ-specific response was in line with previous studies and indicates that the immune microenvironments of different organs often differ [4,5,13,20,21]. Further large cohort-based, long-term followup studies are anticipated to determine whether the response patterns to immunotherapies are clinically relevant.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study demonstrated that the tumor response to PD-1 inhibitors in HCC varied among different organs ( Table 2). This diversity of organ-specific response was in line with previous studies and indicates that the immune microenvironments of different organs often differ [4,5,13,20,21]. Further large cohort-based, long-term followup studies are anticipated to determine whether the response patterns to immunotherapies are clinically relevant.…”
Section: Discussionsupporting
confidence: 85%
“…All measurements were conducted by two skilled radiologists using the axial image data according to the RECIST 1.1 and mRECIST. For organ-specific response criteria, modified from RECIST 1.1, a maximum of two measurable target lesions per organ was allowed to evaluate the response to immunotherapies for tumors of individual organ systems [13].…”
Section: Radiological Analysesmentioning
confidence: 99%
“…Enhanced immune activity in lymph nodes and lung has been proposed as the cause for better tumor control in these tissues compared to liver, adrenal glands, and bone in a study analyzing organ-specific response patterns in IO-treated NSCLC [32]. Since lymph nodes and lung are also very frequent sites of metastatic involvement in NSCLC, it is not surprising that they showed a higher frequency of OPD in our series ( Table 2).…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, nine out of 12 patients with BoM had progressive bone lesions at the time of overall tumor progression. 25 Thus, we performed the present study to investigate whether BoM influences the efficacy of ICI treatment in patients with advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%